Caveolae-mediated Tie2 signaling contributes to CCM pathogenesis in a brain endothelial cell-specific Pdcd10-deficient mouse model - Huanjiao Jenny Zhou (Nature Portfolio, 2021)
Animal models that fully recapitulate human CCM pathogenesis are not currently available. Here, the authors establish a novel CCM model and reveal that caveolae-Tie2 signaling is involved in CCMs formation at the level of venules, which is accompanied by gradual dissociation of pericytes.